Інформаційно-рекламне забезпечення органів місцевого самоврядування - Принда, Василина; Сєров, Юрій (Видавництво Львівської політехніки, 2018)
The article considers the issues associated with providing local governments communication with the community. Described printed information products, which would inform the society and formed their opinion, as well as the questions on the development of the website of the local authority.
Keywords: інформаційно-рекламне забезпечення; інформація; реклама; веб-сайт; наповнення сайту; електронне урядування